The Nevada Water Law of 1913: A Populist Response to Progressivism. - McFarlane, Richard A. (American Journal of Economics & Sociology, 2019)
During the latter half of the 19th century, Americans who settled the arid West needed to compromise with their populist notions of individualism derived from the Jeffersonian ethic of the early 19th century and adopt progressive communitarian practices in order to provide water by means of irrigation. The struggle to deal with water rights in Nevada, culminating in passage of the Nevada Water Law of 1913, particularly illustrated this conflict between individualism and communitarianism.